ANTHOCYANINS, CAROTENOIDS AND ANTIOXIDANT ACTIVITY OF COLOURED COMMERCIALLY AVAILABLE JUICES - BUNEA, Andrea; ANDREI, Sanda; EL-MAHDI, Cristina; CUCERDEAN, Alina; BORA, Florin Dumitru; DIACONEASA, Zorita; PINTEA, Adela (Studia Universitatis Babeș-Bolyai Chemia, 2019)
The phytochemical composition of apple, cranberry, pomegranate, carrot, and beetroot juices was determined in terms of carotenoids, anthocyanins, betalains and ascorbic acid concentration. Antioxidant potential of these beverages was also assessed using the colorimetric DPPH radical scavenging assay. The results showed that pasteurized and unpasteurized carrot and apple juices contain significant amount of β-carotene and cis-β-carotene. High total betalain content was observed in beetroot juice. Major anthocyanins detected in cranberry and pomegranate juices were glycosides of cyanidin, malvidin, and delphinidin. Notable ascorbic acid content and antioxidant potential were observed in unprocessed carrot juices, while beetroot juice exhibited the highest percentage of free radical inhibition.